Strengthening Cybersecurity Protocols to Safeguard U.S. Financial Infrastructure Against Emerging Threats - Alam, Md Ashraful; Sarna, Sanjida Akter; Rakibuzzaman, Md; Reza, Jafrin (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study examines the escalating cybersecurity threats facing the U.S. financial sector between 2020 and 2025, with a focus on identifying emerging attack patterns and proposing strategic responses to protect critical financial infrastructure. Research Design and Methodology: This study employs a mixed-methods approach, combining qualitative analysis of high-profile cyber incidents, such as ransomware and Advanced Persistent Threats (APTs), with quantitative data from cybersecurity reports and institutional records. The methodology includes expert interviews, case study reviews, and statistical analysis to assess the effectiveness of cybersecurity measures. Findings and Discussion: The research reveals that ransomware and advanced persistent threats (APTs) have resulted in significant financial losses, operational disruptions, and reputational damage for financial institutions. The adoption of advanced encryption technologies, Zero Trust Architecture (ZTA), and AI/ML-based threat detection was found to reduce the impact of breaches significantly. Moreover, institutions with integrated cybersecurity strategies and strong public-private collaboration demonstrated greater resilience against cyber threats. Implications: The study underscores the necessity for adaptable, multi-layered cybersecurity frameworks that extend beyond mere compliance. Practical recommendations include ongoing employee training, investment in advanced security systems, and enhancing collaboration with regulatory agencies. These findings provide a roadmap for institutional leaders and policymakers to reinforce the stability and security of the financial sector.